Death and Non-Death Grief Experiences of Filipino College Students - Pamplona, Myla Pilar (JPAIR Multidisciplinary Research, 2023)
The experience of grief because of the loss of loved ones during the COVID-19 pandemic and the loss of control resulting from uncertainties and broken relationships were among the concerns experienced by college students in the past two years. The study aims to understand the grief experiences of Filipino young adults and how they can be utilized to help others. An Interpretative Phenomenological Analysis (IPA) was utilized to understand the death and non-death experiences of three Filipino college students experiencing grief. An in-depth interview was conducted, and the steps using the IPA framework were carefully followed, which included reading and rereading, initial noting, developing emergent themes, searching for connections across emergent themes, moving to the following cases, and looking for patterns across issues. A conceptual framework based on the students’ experiences was developed, and recommendations were crafted. Themes include roller-coaster emotions and coping, connecting symbols to death, finding meaning to experience, remembering loved ones’ wishes, loneliness, and emptiness of missed presence. The recommendation includes creating a Grief Program for Students aligned to their perceived needs.